Including Students With Visual Impairments in Local Schools of Ethiopia: Availability of Resources and Support Services - Ermias Kibreab Tesfaye; Belay Hagos Hailu
Introduction: This study assessed the availability of resources and school supports for students with visual impairments who were mainstreamed in local primary and secondary schools of Addis Ababa, Ethiopia. Methods: A qualitative research approach was used where a semi-structured interview was the tool for gathering primary data from students with visual impairments and special needs education specialists at inclusive education resource centers at the sampled schools. A total of 13 students (5 male, 8 female) with visual impairments were drawn from 2 primary and 4 secondary schools. To ensure the credibility of the study findings, a triangulation of sources and member checks were used. Results: Establishment of inclusive education resource centers and deployment of special needs education specialists were considered promising practices in improving the quality of inclusive education at local schools. Some efforts, like pairing students with visual impairments with sighted peers and administering examinations by subject teachers, need to be strengthened at schools. Multiple challenges were also identified including shortage of resources like textbooks and reference books in braille, braille writing materials, and audio materials. Students with visual impairments encountered challenges during examinations and assignments. The level of support provided by inclusive education resource centers was also found to be below expectations. Discussion: The findings of the current study support previous research in the area, in which students with visual impairments were found to face challenges in accessing resources and appropriate supports. In contrast to earlier findings, however, the current study documented relatively better support for students with visual impairment from sighted peers. Implications for Practice: Policymakers need to closely follow up and check the implementation of various policies and working documents prepared to promote quality inclusive education. Educators and families of students with visual impairments can also use these findings to advocate for improved services.